Espaço 4.0: contribuições para a aprendizagem dos discentes no ambiente Maker do Instituto Federal de Alagoas - Albuquerque, Cassiano Henrique de (2025)
This thesis analyzes the contributions of the “Espaços 4.0” at the Federal Institute of Alagoas (IFAL) to students' Maker Learning, with a focus on the role of monitors in this innovative educational context. The study investigates how innovative environments that integrate Fourth Industrial Revolution technologies with active methodologies contribute to the teaching-learning process. The central question is: How do IFAL’s Espaços 4.0 contribute to the initial and continuing education of young people through Maker Learning? The research aims to understand the effects of these spaces on student development, highlighting the relationship between Maker practices and the acquisition of skills essential for Society 4.0. The FE Classification (Purpose and Structure) was developed, introducing a new categorization for Brazilian Maker Spaces, along with the TMI-E Model (Think, Make, Improve, Explore), which expands the traditional TMI model (Think, Make, Improve) by including the "Explore" phase. The methodology followed a mixed approach, including a Systematic Literature Review and field research conducted in six IFAL campuses, involving students aged 15 to 29 and the monitors of the Espaço 4.0 project. Data collection was carried out through questionnaires and reports, and analyzed using descriptive and inferential statistics, as well as coding cycles. The results indicate that the Espaços 4.0 foster autonomy, creativity, technical and collaborative skills, as well as critical reflection and continuous exploration. Students showed significant progress in problem-solving and practical engagement, with active support from monitors who played a key role in knowledge mediation and project facilitation. Despite the positive outcomes, challenges related to infrastructure and limited resources were reported, affecting motivation and performance. Gender, racial, and income disparities also highlight the need for more inclusive educational policies. The experience of the Espaços 4.0 demonstrated a significant contribution to communities with limited access to innovation, helping to broaden the democratization of knowledge and reduce social inequalities. It is concluded that IFAL’s Espaços 4.0 plays a transformative role in the education of young people in Alagoas, preparing them for Society 4.0 and helping to reduce educational inequalities. The research offers replicable models for institutions, suggesting future investigations into the long-term impacts of these spaces.